Breastfeeding peer counselling for mothers of preterm neonates: protocol of a stepped-wedge cluster randomised controlled trial. Issue 1 (30th January 2020) - Laborie, Sophie; Denis, Angelique; Horsch, Antje; Occelli, Pauline; Margier, Jennifer; Morisod Harari, Mathilde; Claris, Olivier; Touzet, Sandrine; Fischer Fumeaux, Celine Julie
Abstract : Introduction: Among preterm infants, mother's own milk feeding reduces neonatal morbidity and decreases the length of hospital stay. However, breastfeeding rates and duration are lower than among term infants. It is reported that peer counselling is effective in increasing breast feeding in term infants in low-income and middle-income countries, but results are mixed in high-income countries. We aim to investigate herein whether peer counselling may be a feasible and effective breastfeeding support among preterm infants in French-speaking high-income countries. Methods and analysis: Eight European centres will participate in this stepped-wedge cluster randomised controlled trial. We plan to include 2400 hospitalised neonates born before 35 gestational weeks. Each centre will begin with an observational period. Every 3 months, a randomised cluster (centre) will begin the interventional period with peer counsellors until the end of the study. The counsellors will be trained and supervised by the trained nurses. They will have a weekly contact with participating mothers, with a face-to-face meeting at least once every fortnight. During these meetings, peer counsellors will listen to mothers' concerns, share experiences and help the mother with their own knowledge of breast feeding. The main outcome is breastfeeding rate at 2 months corrected age. Secondary outcomes are breastfeeding rates at hospital discharge and at 6 months, breastfeeding duration and severe neonatal morbidity and mortality. The mental health of the mother, mother–infant bonding and infant behaviour will be assessed using self-report questionnaires. A neurodevelopmental follow-up, a cost-effectiveness analysis and a cost–consequence at 2 years corrected age will be performed among infants in a French subgroup. Ethics and dissemination: French, Belgian and Swiss ethics committees gave their agreement. Publications in peer-reviewed journals are planned on breast feeding, mental health and economic outcomes. Trial registration number: NCT03156946